Pengaruh cara pengeringan daun salam (Eugenia polyantha Wight.) Terhadap kadar kolesterol total serum tikus jantan galur wistar hiperlipidemia - Yulianis, Yulianis; Sari, Fitri Pramita; Wahyuni, Fatma Sri (Tropharm (Trobosan Pharmacy), 2015)
A study concerning the drying effect of leaves (Eugenia polyantha Wight ) against levels serum total cholesterol of male rats wistar hyperlipidemia. Research conducted of test animals on rats wistar strain male  induced by fat cows, quail egg yolk (ratio 1:5) and added  PTU as much 0.1% of a mixture both of them, so that the test animals  become hyperlipidemia. As many as 16 test animals were divided into four groups tails. Group I was given a suspension NaCMC extracts of fresh bay leaves, group II was given a suspension NaCMC extract of dried leaves in the open air, group III was given a suspension from leaf extracts NaCMC oven dried, and the fourth group was given a solution of NaCMC without leaf extract. The study was conducted by giving suspension of  leaf extract at a dose of 0.72 g / kg bw orally to the test animals. Observations of total serum cholesterol carried on day 8 after the acclimatization, the 22nd day after the induction of hyperlipidemia, and day 37 after administration of the extract. results test of Two-way ANOVA  showed that the extracts from fresh leaves and dried leaf extract air giving effect is hardly much different or almost the same on 41.761% and 39.058%, and a decrease in serum total cholesterol of  least of low indicated by the extracts of oven dried leaf  on 5.781%.